Acidic ionic liquid based UiO-67 type MOFs: a stable and efficient heterogeneous catalyst for esterification. Issue 18 (13th March 2018) - Xu, Zichen; Zhao, Guoying; Ullah, Latif; Wang, Meng; Wang, Aoyun; Zhang, Yanqiang; Zhang, Suojiang
Abstract : Acidic ionic liquid groups were introduced into the frameworks successfully and the resulting materials showed excellent activity. Abstract : A facile strategy for the synthesis of acidic ionic liquid based UiO-67 type MOFs was developed in this study. Brønsted acids (H2 SO4, CF3 SO3 H and hifpOSO3 H (hexafluoroisopropyl sulfuric acid)) were introduced into UiO-67–bpy (bpy = 2, 2′-bipyridine-5, 5′-dicarboxylic acid) frameworks by reacting with bipyridyl nitrogen to introduce the properties of an acidic ionic liquid into the frameworks. The prepared catalysts, denoted as UiO-67–HSO4, UiO-67–CF3 SO3 and UiO-67–hifpOSO3, were characterized by XRD, SEM, FT-IR, EA, TGA and N2 adsorption–desorption studies. The relatively high surface area was still maintained and acidic active groups were uniformly dispersed in the frameworks. The catalytic performance of UiO-67–HSO4, UiO-67–CF3 SO3 and UiO-67–hifpOSO3 was evaluated by the esterification of acetic acid with isooctyl alcohol. The prepared catalysts showed good catalytic activities in the esterification, of which UiO-67–CF3 SO3 gave the maximum isooctyl alcohol conversion of 98.6% under optimized conditions. The catalyst could be reused five times without a significant decrease in the conversion of isooctyl alcohol, and almost no active species were leached, indicating the excellent stability and reusability of the catalyst. Our study provides one effective way to synthesize heterogeneous acidic ionic liquid catalysts consisting of isolated, well defined acidic groups that will probably attract interest in acid catalyst chemistry.